Gambaran Implementasi Kursus Pranikah di Kabupaten Grobogan, Jawa Tengah, Indonesia: Implementation of Premarital Counseling Description in Grobogan District, Central Java, Indonesia - Sri Achadi Nugraheni; Atik Mawarni; Cahya Tri Purnami; Sri Winarni; Alfi Fairuz Asna; Apoina Kartini; Septo Pawelas Arso; Novia Handayani; Naila Fauziatin (Amerta Nutrition, 2023)
Background: Pre-marital period is the best time to prepare for the quality of family health; however, In Indonesia, examinations and promotion of reproductive health and pre-marital counseling have yet to be carried out in all districts. Objectives: This study aimed to identify the description of reproductive health services and marriage counseling in Grobogan Regency, Central Java. Methods: This study used an assessment method of the implementation of the Reproductive Health Service Program for the bride, which includes IEC (Communication, Information, and Education) and medical examination of the bride and groom by health workers conducted in community health centers (Puskesmas) and other health care facilities, and office of religious affair (KUA), with the In-depth Interview Method. The subject was the KUA Officer under the Department of Religious Islamic Education in the Marriage Guidance program. Results: The interviews with KUA officers obtained results in 2017. There were still underage marriages, and the number increased in 2018. Prospective brides have submitted forms (N1, N2, N3, and N4) to KUA. Most of the brides were not physically examined (pulse, breathing frequency, blood pressure, body temperature) by health workers (63.7%), and blood groups were not examined (91.4%). Half of the respondents examined blood sugar, HIV, IMS, Hepatitis, and TORCH (56.8%). The bridegrooms were not examined for mid-upper arm circumferences (MUAC) (17.2%) and for signs of anemia (8.6%). The brides were not immunized against Hepatitis B (72.4%). Almost all brides get TT immunization at the Puskesmas (94.8%). Health workers stated that only some brides had been getting counseling about the bride's mental health (29,3%). Only 17.2% of the officers stated that the bride still needs to get a certificate of following the reproductive health IEC. Conclusions: KUA has conducted pre-marriage courses for couples according to the rules of the Ministry of Religion. Some PUSKESMAS had carried out activities for the bride and groom on a scheduled basis (for example, every Tuesday/Wednesday) but have not been carried out routinely, even stopped due to budgetary problems. The certificate is given after the bride and groom take the marriage guidance course, but it has yet to be required for marriage registration.